The Authority of the Indonesian Maritime Security Agency in Enforcing Law within Indonesian Waters - Febri Gumelar; Aris Prio Agus Santoso; Muhamad Habib (Eastasouth Institute, 2026)
Indonesia has established a comprehensive legal framework governing the authority of the Indonesian Maritime Security Agency (Bakamla) in maintaining maritime security and enforcing law at sea, as regulated under Law Number 32 of 2014 on Maritime Affairs and international instruments such as the United Nations Convention on the Law of the Sea. However, in practice, maritime law enforcement in Indonesian waters faces significant challenges, particularly overlapping institutional authorities and weak inter-agency coordination. This study aims to analyze the implementation of Bakamla’s authority and identify the juridical constraints encountered. It adopts a normative juridical approach using secondary legal materials, analyzed qualitatively through a deductive method. The findings reveal that Bakamla’s authority has strong legal legitimacy based on the 1945 Constitution, relevant laws, government regulations, and presidential regulations. Bakamla is authorized to conduct maritime patrols, monitor territorial waters, undertake initial law enforcement actions, and coordinate with institutions such as the Indonesian Navy and the National Police. Nonetheless, its implementation is hindered by fragmented authority, limited investigative powers, differing institutional legitimacy, and inadequate regulatory harmonization. Strengthening coordination and integrating maritime law enforcement systems are therefore essential to improve the effectiveness of safeguarding Indonesian waters.